ANALISIS PRODUKTIVITAS SEKOLAH MENENGAH ATAS NEGERI (SMAN) DI KABUPATEN SEMARANG - Khoirul Lathifah, Hanis; Dwi Atmanti, Hastarini (Diponegoro Journal of Economics, 2013)
The aim of this study is to analyze technical efficiency in education sector with case study in 11 Public Senior High School (SMAN) at Semarang Regency in academic year 2008/ 2009 up to 2011/ 2012. This study applying Data Envelopment Analysis (DEA). DEA is designed as a specific to measure relative efficiency a productical unit which is using multi input and output, that commonly difficult to investigate perfectly when using the others analytical technic measurement. A productical unit’s relative efficiency is comparison of efficiency between productical unit with the other in sample which are using the same kind of input and output. This study use Data Envelopment Analysis (DEA) method, which is using Variabel Return to Scale (VRS) assumption. The input variable was representated by student teacher ratio, student class ratio, student administrative staff ratio, teacher education ratio, and ratio of the teacher experience. Output variable consist of the average value of national exam, the percentage of graduation rates, and the percentage increase in the number of the class.The study show that there are several Decision Making Units (DMU) which have perfect efficiency, they are SMAN 1 Getasan, SMAN 1 Tengaran, SMAN 1 Suruh, SMAN 1 Susukan, SMAN 1 Pabelan, SMAN 1 Tuntang, SMAN 1 Ambarawa, SMAN 1 Ungaran, dan SMAN 2 Ungaran. Sensitivity test in this study aims to determine the DMU, which became the best reference. By ignoring one of the inputs, an efficient DMU is SMAN 1 Pabelan, SMAN 1 Susukan, SMAN 1 Ambarawa, SMAN 1 Ungaran, and SMAN 2 Ungaran. If one and some DMU ignored, all efficient DMU remain efficient.